Tri Hita Karana Values In The Implementation Of Quality Tourism In Sidetapa Village (Journal of Namibian Studies : History Politics Culture, 2023)
The Covid-19 pandemic hit Bali's tourism sector in 2020 by at least 80%. In 2021, various travel restrictions will begin to be relaxed, thereby opening up the potential for tourism revival and economic recovery. This needs to be supported by the right tourism concept and based on local wisdom. This condition also occurs in the Bali Aga community in Sidetapa village, Buleleng district. This study aims to: (1) analyze the value of local wisdom Tri Hita Karana of the Balinese Aga community in Sidetapa Village; (2) Explore tourism potential in Sidetapa village based on the concept of quality tourism; (3) Integrate the value of local wisdom Tri Hita Karana in the implementation of quality tourism in Sidetapa village. The results showed that the local wisdom of Tri Hita Karana has three values, namely Parhyangan, Pawongan, and Palemahan. Quality tourism is a tourism concept that emphasizes the quality of experience, and the length of time tourists visit and not just the number of tourist visits. Sidetapa Village has several tourism potentials that are in line with the concept of quality tourism in the form of natural, cultural, and educational tourist attractions, as well as various activities and other supporting facilities. The integration of Tri Hita Karana's local wisdom in quality tourism is realized through (1) the parhyangan aspect being integrated through the implementation of traditional ceremonies as a tourist attraction without reducing the sacred aspect of the ceremony; (2) the pawongan aspect is integrated through cross-sectoral cooperation in the pentahelix element to support the competency development of the Bali Aga community in the village of SIdetapa in the field of tourism and branding of the village's tourism; (3) the palemahan aspect is integrated through environmental conservation to realize ecotourism so that it can attract tourists to enjoy the uniqueness and natural preservation of Sidetapa village.